2017
DOI: 10.1080/15438627.2017.1365295
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of back/neck/spine injuries in National Collegiate Athletic Association men’s and women’s ice hockey, 2009/2010 to 2014/2015

Abstract: This study describes the epidemiology of back/neck/spine injuries in National Collegiate Athletic Association (NCAA) men's and women's ice hockey. Data from 66 NCAA men's and 29 women's ice hockey programmes (total of 147 and 67 team-seasons, respectively) were analysed from the NCAA Injury Surveillance Program during the 2009/2010-2014/2015 academic years. In the study period, 226 and 97 back/neck/spine injuries were reported in men and women, respectively, for injury rates of 0.56 and 0.65/1000 athlete expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(33 citation statements)
references
References 18 publications
2
30
0
1
Order By: Relevance
“…6 Previous studies have shown LSIs to be the most common in NCAA ice hockey. 25 Understanding the frequency, rates, types, chronicity, mechanism of injury, and time loss in both men’s and women’s college basketball and comparing the results according to sex can help address these injuries with the goal of making basketball safer for these athletes. Epidemiological studies of National Basketball Association (NBA) injuries from 1988 to 2015 showed that LSIs occurred at a rate of 34 per 10,000 AEs (n = 1279; 10.2% of all injuries reported).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Previous studies have shown LSIs to be the most common in NCAA ice hockey. 25 Understanding the frequency, rates, types, chronicity, mechanism of injury, and time loss in both men’s and women’s college basketball and comparing the results according to sex can help address these injuries with the goal of making basketball safer for these athletes. Epidemiological studies of National Basketball Association (NBA) injuries from 1988 to 2015 showed that LSIs occurred at a rate of 34 per 10,000 AEs (n = 1279; 10.2% of all injuries reported).…”
Section: Discussionmentioning
confidence: 99%
“…Despite how common LSIs are in collegiate athletes, there is a paucity in the literature on these injuries in collegiate basketball athletes, and no study has analyzed sex-based differences in this population. 2,8,25 The purpose of this study was to analyze the National Collegiate Athletic Association (NCAA) Injury Surveillance Program (ISP) database from the 2009-2010 to 2013-2014 academic years to describe and compare the epidemiology of LSIs in women’s and men’s college basketball.…”
mentioning
confidence: 99%
“…Three studies 7,8,9 scored ≤13/20 indicating a risk of bias. The remaining articles 1,2,3,4,5,6 scored above 14/20, resulting in a rating of high quality. These studies suggest that the strengthening of neck musculature may reduce the velocity and acceleration of the head during body impact.…”
Section: Clinical Bottom Linementioning
confidence: 99%
“…Injury data collected from collegiate ice hockey teams throughout the period of 2009 to 2015 revealed the prevalence of 323 back, neck, and spinal injuries. 3 Of these injuries, many were localized to the lumbar spine occurring during competition, indicating that cervical spine injuries were not common. Findings revealed mixed evidence supporting the occurrence of cervical spine injuries within ice hockey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation